Back Cover: Photoelectrochemical Water Oxidation Efficiency of a Core/Shell Array Photoanode Enhanced by a Dual Suppression Strategy (ChemSusChem 9/2015). Issue 9 (4th May 2015) - He, Wanhong; Yang, Ye; Wang, Liren; Yang, Junjiao; Xiang, Xu; Yan, Dongpeng; Li, Feng
<x xml:space="preserve">Abstract</x> The Back Cover picture shows a core/shell array photoanode and its application in photoelectrochemical water oxidation. The photoanode consists of a TiO2 nanorod array (core) and ultrathin phosphated double‐hydroxide (shell), which results in significantly improved photogenerated carrier separation. Nearly 100 % oxidative efficiency for PEC water oxidation was achieved. In addition, the hydroxide sheath could efficiently inhibit the oxygen reduction reaction. This strategy enables the simultaneous suppression of surface carrier recombination and back reactions, which is promising to enhance the water oxidation efficiency of the currently prevailing photoanodes. More details can be found in the Full Paper by He et al. on page 1568 (DOI: 10.1002/cssc.201403294).